Child-centered play therapy a clinical session - Landreth, Garry; Play Therapy Institute ([Texas] : Play Therapy Institute, 1997)
This complete and unrehearsed play therapy session demonstrates the process of building a relationship with a child, following the child's lead, facilitating the development of children's strengths, responding to accidents in the playroom, building a child's self-esteem, returning responsibility to the child, participation in a child's play without structuring, empowering children, and dealing with a child reluctant to leave the playroom
Title from title screen
Title from title screen
DVD Format
Keywords: Play therapy; Cognitive therapy for children; Child psychotherapy; Cognitive therapy